Penerapan Regresi Linear dalam Perkiraan Harga Beras di Kota Bengkulu - Azhar Dyo Pramono; Herlina Latipa Sari; Ila Yati Beti (IAI Nasional Laa Roiba Bogor, 2024)
The price of rice tends to fluctuate or change, therefore it is necessary to predict the price in the next period as an effort to maintain the stability of the average price of rice in the community. In Bengkulu City, there are 6 types of rice, namely IR 64 Lampung Local Rice (Medium), IR 64 Bengkulu Local Rice (Medium), Manggis Manis Rice (Premium), Kembang Kol Rice (Premium), Termurah Rice (medium), Bulog/Dolog rice. The implementation of linear regression in rice price forecasting in Bengkulu City can help provide an overview of the estimated price of rice in the next 1 year from January to December based on the results of processing time series data on previous rice prices through Linear Regression Method and can help people to minimize losses and maximize profits, especially for the business and economic sectors. Based on the test results of rice price data from 2021 to 2023, the average results of rice price forecasting on 6 types of rice in 2024 are IR 64 Lampung Local Rice (Medium) with a prediction of IDR 12,202, IR 64 Bengkulu Local Rice (Medium) with a prediction of IDR 12. 094,-, Manggis Manis Rice (Premium) with a prediction of Rp 14,876,-, Kembang Kol Rice (Premium) with a prediction of Rp 15,032,-, Termurah Rice (medium) with a prediction of Rp 11,437,-, Bulog/ Dolog rice with a prediction of Rp 10,900,-.